"You Don't Get Respect if You Give No Respect": How Black and Latino Youth Make Sense of Encounters with Police. Issue 1 (2nd January 2017) - Rengifo, Andres F.; McCallin, Morgan
ABSTRACT: The study documents opinions about the police among black and Latino youth and explores how these assessments reflect differences in lived experiences and frames of interpretation of police encounters across gender and race/ethnicity. This specification is important to better understand how youth navigate interactions with law enforcement and how discrete experiences are interpreted in the context of other contacts of racial and gender inequality. We draw on interviews with 43 black and Latino youth, ages 13–21, compiled as part of a project on police stops in New York City. Although our findings indicate that youth tend to see the police negatively, we note considerable heterogeneity, with Latinos/as conveying more mixed views of law enforcement and females signaling more negative perceptions. We tie these differences to variation in the type, volume, and quality of encounters with the police, as well as the saliency of direct and indirect experiences.